REVITALISASI ISLAM KULTURAL - Jamil, M. Mukhsin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
This research aim to explore one of Islamic movements in Indonesia after reformation of 1998. By using qualitative method, it is clear that the demarcation betweeen Islamic tradisionalism and Islamic modernism fluided culturally. Although at the same time polarization both become more political, which is made Indonesian Islamic mainstream loosed elan vital as sosial and cultural movement. There is the contradictory trends in the dynamic of Islamic thought and movement introduced by Islamc minority groups. In one side the trends are multiculturalism, anti coruption movement and appreciation to the local cultures which is ignorenced before by Islamic movement in Indonesia. In other side, political oriented in many Islamic movement is stronger. The dominant of traditional constructions of Islamic polical thought of sunni (fiqh al-siyasah) influenced to the Islamic movement to state orientation at same time ignored the society with their problem and cultural expression. The cultural Islam proposed new understanding to Islamic traditions with hermeneutic and remove the locus of movement forum political Islam to civil Islam.***Penelitian ini bertujuan untuk menjelajahi salah satu gerakan Islam di Indonesia setelah reformasi 1998. Dengan menggunakan metode kualitatif, akan menjadi jelas demarkasi antara Islam tradisional dan Islam modernis secara kultural. Meski polarisasi kedua kelompok keagamaan itu kerap bernuansa lebih politis, sehingga menghilangkan elan vital Islam Indonesia sebagai gerakan sosial dan budaya. Tetapi ada tren kontradiktif dalam dinamika pemikiran dan gerakan Islam yang dilakukan oleh kelompok minoritas Islam. Di satu sisi trennya adalah multikulturalisme, gerakan anti korupsi, dan apresiasi terhadap budaya lokal yang telah dikembangkan oleh gerakan Islam sebelumnya. Di sisi lain, orientasi politik kelompok keagamaan juga semakin meningkat. Dominasi pemikiran politik tradisional Sunni turut mempengaruhi pola gerakan Islam kepada negara dan pada saat yang sama mengabaikan masyarakat dengan problem kebudayaan mereka. Islam kultural mencoba untuk meniupkan pemahaman baru dalam tradisi Islam dengan hermeneutika dan menggeser arah gerakan Islam politik kepada Islam sipil.